(3QSGdI aj JRcjI GdfaSs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3ai JRcjI GdfaS ddTjN GdQFjS dJNQLgG ef GdbhI Edi GdaYd YGdekG ef YhGde GdYbd s
(3BNQgG (B:s
(3ai Gdedc GdCRdi hedcI GdfaS Yf ZfGA GdfGS jSjQ HgPg GdSjOg hjjf HgPg GdOjGfI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B(9)41) s
Keywords: (3GdadSaI hGdefWbs